Interdisciplinary Medicine - Diaconu, Camelia (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Dear Colleagues, The rapidly changing field of medicine and healthcare is increasingly adopting scientific and technological innovations, making interdisciplinary collaborations especially important. In this context, medical disciplines are becoming increasingly interlinked with other specialities and fields. A more interdisciplinary approach to the patient is needed, especially for complex patients with numerous comorbidities, most of whom are usually elderly and fragile. The greatest challenges to human health lie at the intersection of different medical fields. An interdisciplinary medical team is increasingly necessary with the rapid expansion of medical knowledge. Given the importance of interdisciplinarity in the field of medicine and research, the international journal Medicina-Lithuania has launched this Special Issue. The Special Issue has attracted the interest of different groups of researchers, and very interesting articles from different countries. Reviews or original articles dealing with interdisciplinary medical problems, as well as articles providing an up-to-date overview of the diagnostic protocols and treatments for patients with multiple comorbidities have been published. I thank all the authors for sharing their research and wish all readers a fruitful and stimulating read! Assoc. Prof. Dr. Camelia DIACONU Guest Editor